THE INFLUENCE OF HALAL LITERACY, HALAL LABELING, PRODUCT QUALITY, AND PRICE ON SKINCARE PURCHASING DECISIONS: THE MEDIATING ROLE OF WILLINGNESS TO PAY A PREMIUM PRICE - Karimah, Alfiatul; Dahruji (Universitas Muhammadiyah Surabaya, 2024)
The growing awareness of the importance of halal products has significantly influenced various sectors, including the cosmetics industry. However, prior research has predominantly focused on halal food and beverages, while halal skincare products, such as Somethinc, have received limited academic attention. Furthermore, studies that integrate halal literacy, labeling, product quality, and price about purchase decisions, with a willingness to pay a premium price as a mediating variable, remain scarce. This study examines the influence of halal literacy, halal label, product quality, and product price on the purchasing decisions of Somethinc skincare products among Gen Z, mediated by willingness to pay a premium price. The research method used is quantitative, with primary data obtained through questionnaires. The sampling was conducted using purposive sampling, with a total of 272 respondents. The data analysis technique used is Structural Equation Modeling (SEM), analyzed using the software SmartPLS version 3. The results of this study indicate that the variables halal literacy, product quality, and product price do not directly affect purchasing decisions, while the halal label variable and willingness to pay a premium price directly influence purchasing decisions. The halal literacy and halal label variables do not affect willingness to pay a premium price, whereas product quality and product price variables do affect willingness to pay a premium price. Additionally, halal literacy and halal labels do not influence purchasing decisions when mediated by a willingness to pay a premium price, whereas product quality and product price do influence purchasing decisions when mediated by a willingness to pay a premium price.